An Updated View on the Antiviral Therapy of Hepatitis C in Chronic Kidney Disease - Fabrizio Fabrizi (MDPI AG, 2021)
Background: Hepatitis C virus infection remains common in patients with chronic kidney disease, including those on maintenance dialysis. The relationship between hepatitis C virus infection and chronic kidney disease is bi-directional; in fact, HCV is both a cause and consequence of chronic kidney disease. According to a systematic review with meta-analysis of observational studies (n = 23 studies) (n = 574,081 patients on long-term dialysis), anti-HCV positive serologic status was an independent and significant risk factor for death in patients with advanced chronic kidney disease on long-term dialysis. The overall estimate for adjusted mortality (all-cause death risk) with HCV was 1.26 (95% CI, 1.18; 1.34) (p < 0.0001). Interferon-based therapies are biased by low efficacy/safety in chronic kidney disease, but the advent of direct-acting antiviral drugs has made a paradigm shift in the treatment of HCV-infection. These medications give interruption of viral replication because they target specific non-structural viral proteins; four classes of DAAs exist-NS3/4A protease inhibitors, NS5A inhibitors, NS5B nucleoside and non-nucleoside polymerase inhibitors. All-oral, interferon-free, ribavirin-free combinations of DAAs are now available. Aim: The goal of this narrative review is to report the available treatment options for HCV in advanced chronic kidney disease. Methods: We have made an extensive review of the medical literature and various research engines have been adopted. Results: Some combinations of DAAs are currently recommended for HCV in advanced CKD (including patients on maintenance dialysis): elbasvir/grazoprevir; glecaprevir/pibrentasvir; and sofosbuvir-based regimens. Solid evidence, based on registration and “real life” studies supports their efficacy (SVR rates > 90%) and safety even in patients with advanced CKD. No dosage adjustment is necessary and treatment duration is 8–12 weeks. However, recent data highlight that many patients with advanced CKD remain untreated, and numerous barriers to antiviral treatment of HCV still exist. Whether successful antiviral therapy with DAAs will translate into improved survival in the advanced CKD population is another point of future research.